The geography and land use changes in the Río Grande micro - basin, (2005-2017) - Arias Rodríguez, Jarol (2026)
In the Río Grande micro-watershed, land use changes alter the hydrological response in various r sections of the river, diminishing the transport capacity for surplus runoff, which is intensified by soil sealing.  It’s relevant to identify the geographic area’s land cover to understand the economic foundation of the population and to identify the transformations present in the terrain. The primary objective of this study is to identify the changes in the land use with a section of the Río Grande micro-watershed for the 2005 - 2017. The methodology implemented is qualitative, employing land cover identification and digitization techniques using orthophotos and QGIS 2.8 software. Complementarily, the polygon topology was processed in ArcGIS 10.5, thereby integrating the capabilities of both programs. The rationale for selecting this time frame is that this year exhibited the most significant decrease in pasture and forest cover, while permanent crops, along with urbanization, showed an increase.